2020
DOI: 10.3390/ijms22010233
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotective Effects of Loganic Acid on Osteoblastic and Osteoclastic Cells and Osteoporosis-Induced Mice

Abstract: Osteoporosis is a common disease caused by an imbalance of processes between bone resorption by osteoclasts and bone formation by osteoblasts in postmenopausal women. The roots of Gentiana lutea L. (GL) are reported to have beneficial effects on various human diseases related to liver functions and gastrointestinal motility, as well as on arthritis. Here, we fractionated and isolated bioactive constituent(s) responsible for anti-osteoporotic effects of GL root extract. A single phytochemical compound, loganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Our results are consistent with our recently published studies showing the antiosteoporotic effects of the cornelian cherry extract containing loganic acid. Park et al [ 8 ] found that loganic acid isolated from Gentiana lutea L. roots extract significantly stimulated osteoblast differentiation by increasing ALP activity and upregulating the mRNA expression of Alpl, Bglap, and Sp7. In animal experiments, extracts from the cornelian cherry ameliorated the harmful changes in the bone turnover markers and bone mineral density (BMD) of hypercholesterolemic-diet rabbits [ 15 ] and counteracted the decrease in BMD and bone flexural strength of ovariectomized mice [ 8 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with our recently published studies showing the antiosteoporotic effects of the cornelian cherry extract containing loganic acid. Park et al [ 8 ] found that loganic acid isolated from Gentiana lutea L. roots extract significantly stimulated osteoblast differentiation by increasing ALP activity and upregulating the mRNA expression of Alpl, Bglap, and Sp7. In animal experiments, extracts from the cornelian cherry ameliorated the harmful changes in the bone turnover markers and bone mineral density (BMD) of hypercholesterolemic-diet rabbits [ 15 ] and counteracted the decrease in BMD and bone flexural strength of ovariectomized mice [ 8 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been proven that bone metabolism can be modulated by nutrients [ 2 , 3 ]. Recently published studies have reported that polyphenols, especially anthocyanins [ 4 , 5 ], phenolic acids [ 6 ], and flavonols [ 7 ], as well as iridoids [ 8 ] and hydrolysable tannins [ 9 ] can prevent bone loss through different mechanisms. All these substances are present in cornelian cherries, in varying amounts, making their extracts promising candidates for antiosteoporotic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Cha, a common component contained in Xuduan, Honghua, and Hujisheng, can exert a neuroprotective effect [ 24 ]. Moreover, as a characteristic component in Xuduan, Loa can achieve an osteoprotective effect [ 25 ]. Cor is one of the major constituents in Laoguancao, which possesses antioxidant, thrombolytic, antiatherogenic, and hepatoprotective properties [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Extraction variables, including extraction solvent (25%, 50%, 75%, and 100% methanol aqueous solution), ratio of material/solvent (1 : 25, 1 : 50, and 1 : 125 g mL −1 ), extraction time (20, 30, and 40 min), and extraction temperature (25,40,50, and 60 °C) were investigated by single-factor experiment to obtain higher extraction efficiency of the tested compounds. To show the optimization process of the extraction method intuitively, the "spider-web" mode proposed by our research group in 2016 [22,23] was applied to comprehensively analyze the effects of different extraction conditions on the extraction efficiency of all the tested compounds, such as Gaa, Pra, Nea, Cha, Cra, Loa, Cor, Log, IaB, IaA, IaC, AnA, Coa, AsD, Ost, and Col. e content of the target compounds was assigned as C m-k ; the maximum content value of each compound in the tested extracting conditions was assigned as C k(max) ; the normalized value of content was assigned as E m-k .…”
Section: Optimization Of Sample Preparation and Chromatographic Condi...mentioning
confidence: 99%
“…Park et al studied the effect of loganic acid on the adipogenesis of 3T3-L1 preadipocytes and cells in ovariectomy-induced obesity model mice and found that loganic acid can prevent the adipocyte differentiation of 3T3-L1 preadipocytes and cells in ovariectomized mice by reducing the expression of adipogenesis-inducing genes to exert an antiadipogenic effect ( Park, et al, 2018 ). Park et al found that loganic acid can increase osteoblast production and upregulated the expression of related genes to induce the differentiation of osteoblasts and prevent the differentiation of primary cultured osteoclasts, indicating that loganic acid may be a potential antiosteoporosis agent ( Park, et al, 2020 ).…”
Section: Classification and Overview Of Secondary Metabolitesmentioning
confidence: 99%